Half-life measurements of stored fully ionized and hydrogen-like 122 I ions - Atanasov, Dinko; Shubina, Daria; Stöhlker, Thomas (The European physical journal. A, Hadrons and nuclei, 2012)
The half-lives of fully ionized and hydrogen-like (H-like) 122I ions have been measured in a heavy-ion storage ring. The β+β+ β^{+}_{} -decay constants for both charge states and the electron capture (EC) decay constant of H-like ions have been determined. The EC-decay constant in H-like 122I ions \ensuremathλH-likeEC=7.35(33)⋅10−4s−1\ensuremathλECH-like=7.35(33)⋅10−4s−1\ensuremath λ^{\text{H-like}}_{\rm EC}=7.35(33)·10^{-4}{\,s}^{-1} is, within the uncertainty, the same as the one in neutral atoms. This result is in agreement with the estimates of recent theoretical considerations on the EC-decay of few-electron ions that explicitly take into account the conservation of the total angular momentum of the nucleus plus lepton(s) system and its projections. No firm confirmation could be concluded from our results on the predicted effect that allowed Gamow-Teller transitions become forbidden if the initial and final total angular momenta are not equal.-1